2020
DOI: 10.3390/vaccines8030436
|View full text |Cite
|
Sign up to set email alerts
|

Natural Self-Ligand Gamma Delta T Cell Receptors (γδTCRs) Insight: The Potential of Induced IgG

Abstract: A γδ T cell acquires functional properties in response to the gamma delta T cell receptor γδTCR signal strength during its development in the thymus. The elucidation of the potential ligands of γδ T cell receptors are of extreme importance; however, they are still not understood. Here we revise the actual state of the art of candidates to exert the function of γδTCR ligands, and propose a theoretical contribution about new potential ligands of γδTCRs, based on biological and hypothetical pieces of evidence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Apart from that, in the past years, some studies have demonstrated that IgG can play a pivotal role in mediating complex interactions that result in functional lymphocyte modulation during maturation in self or offspring primary lymphoid organs and how this implicates in the context of allergy (33,37,(49)(50)(51). These studies proposed several IgG idiotypes interacting with molecules expressed on B-and T-cell membranes during the maturation process, including clonal receptors (BCRs and TCRs).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, in the past years, some studies have demonstrated that IgG can play a pivotal role in mediating complex interactions that result in functional lymphocyte modulation during maturation in self or offspring primary lymphoid organs and how this implicates in the context of allergy (33,37,(49)(50)(51). These studies proposed several IgG idiotypes interacting with molecules expressed on B-and T-cell membranes during the maturation process, including clonal receptors (BCRs and TCRs).…”
Section: Discussionmentioning
confidence: 99%
“…Still, the exact mode is not clear, e.g., Vδ1 cells recognise both empty CD1 molecules, as well as those presenting glycolipid or phospholipid, although in the latter case the affinity is higher [ 60 , 61 ]. Some authors even suggest that IgG antibodies may be considered to be yet another ligand for γδ TCR [ 62 ]. For a wider overview of the topic, we suggest a recent review article by Malte Deseke and Immo Prinz [ 60 ].…”
Section: γδ T Recognition Of Tumour Cellsmentioning
confidence: 99%
“…As IgG production is involved in some essential immunotherapy protocols, this aspect, in the SARS-CoV-2 pandemic period, opens a new and broad field for further exploration. If γδ T cells influence B cells in the opposite direction, it was speculated that γδ T cells are subject to influence by the IgG repertoire, which could act as a ligand of γδ TCR [63].…”
Section: Contribution Of γδ T Cells To Anti-sars-cov-2 Therapymentioning
confidence: 99%